INNOVATIONS AND INNOVATIVE APPROACHES IN THE MANAGEMENT OF EDUCATIONAL INSTITUTIONS - Madaminova Khusnida Rashidovna (American Journals, 2025)
This article examines the extent to which innovative technologies are being used in practice in the education system of Uzbekistan in comparison with the experience of foreign countries.The study examines the clear lack of concepts related to pedagogical innovations, the search for optimal methods of teaching and educating the younger generation in the context of the transition to an adapted educational institution, and the formation of a new field of knowledge - pedagogical innovation.
Keywords: Education, principle, modern education, Innovation, Business, quality, technology, Information, reform.